Arresting fake news sharing on social media: a theory of planned behavior approach. Issue 8 (18th March 2021) - Pundir, Vartika; Devi, Elangbam Binodini; Nath, Vishnu
Abstract : Purpose: This study aims to examine the collective impact of awareness and knowledge about fake news, attitudes toward news verification, perceived behavioral control, subjective norms, fear of missing out (FoMO) and sadism on social media users' intention to verify news before sharing on social media. Design/methodology/approach: The current study's conceptual framework is developed by a comprehensive literature review on social networking and the theory of planned behavior. The data for samples were collected from 400 respondents in India to test the conceptual framework using the partial least square–structural equation modeling technique. Findings: The results show that awareness and knowledge, perceived behavioral control, attitudes toward news verification and FoMO are significant predictors of intention to verify news before sharing. Research limitations/implications: The present study concludes implications for managers of social media companies and policy actors that want to take steps toward arresting the spread of fake news via social media. Originality/value: Academic investigation on fake news sharing on social media has recently gained traction. The current work is unique because it uses the theory of planned behavior as a basis for predicting social media user's intention to verify news before sharing on social media.